Phytochemical constituents and bioassay-guided isolation of an anticandidal compound from albizia myrophylla benth - Adegoke, Damilola Samuel (2015)
Albizia myriophylla Benth is used as a remedy for cough, as an antidiabetic agent and as a starter culture in the preparation of rice beer. This study used a bioassay guided approach to investigate the anti-candidal properties of A. myriophylla and identify compound(s) responsible for the anti-candidal activity. In addition, otherphytoc hemical constituents of the plant were also investigated. Wood extract of A. myriophylla was screened for anti-candidal activity against four Candida species human pathogens: C. albicans, C. krussei, C. parapsilosis, and C.glabrata. Solvent fractionation technique was used to achieve a partition of the extract into four different fractions. Disc diffusion assay was used to determine the presence of anti-candidal activity in the fractions. Bioassay-guided column chromatography separation was used to retain anti-candidal fractions while separating out non-active fractions. Thin layer chromatography (TLC) bioautographic assay was used in an attempt to directly localize the anti-candidal compound(s) in the active fractions. Following this, separation and purification using preparative thin layer chromatography of the active fraction led to the isolation of an anti-candidal compound. Nuclear magnetic resonance spectroscopy and mass spectroscopy were used for the characterization of the isolated compounds. The result showed that an anti-candidal compound was isolated from the chloroform fraction of the aqueous methanol extract of A. myriophylla. The compound, identified to be 4-hydroxy-3,5-dimethoxybenzaldehyde or syringaldehyde, had MIC and MFC values of 0.000056 and 0.020000μg/μL respectively on C. parapsilosis- which was themost susceptible species. Meanwhile, chromatographic work up of the ethyl acetate fraction afforded five flavonoids, three of which were stereoisomeric flavans identified as (2R,3R,4R)-2-(3,5-dihydroxyphenyl)-3,4-dihydro-2H-chromene-3,4,7-triol,(2R,3S,4S)-2-(3,5-dihydroxyphenyl)-3,4-dihydro-2H-chromene-3,4,7-triol and (2R,3R,4R)-2-(3,4-dihydroxyphenyl)-3,4-dihydro-2H-chromene-3,4,7-triol; a flavanone, 2,3-dihydro-7-hydroxy-2-(3,5-dihydroxyphenyl)-4H-1-benzopyran-4-one;and a flavone, 7-hydroxy-3-methoxy-2-(3,4-ihydroxyphenyl)-4H-1-benzopyran-4-one.